2020
DOI: 10.1093/nar/gkaa306
|View full text |Cite
|
Sign up to set email alerts
|

GeneTrail 3: advanced high-throughput enrichment analysis

Abstract: We present GeneTrail 3, a major extension of our web service GeneTrail that offers rich functionality for the identification, analysis, and visualization of deregulated biological processes. Our web service provides a comprehensive collection of biological processes and signaling pathways for 12 model organisms that can be analyzed with a powerful framework for enrichment and network analysis of transcriptomic, miRNomic, proteomic, and genomic data sets. Moreover, GeneTrail offers novel workflows for the analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 28 publications
0
76
0
Order By: Relevance
“…Concerning the functions of the identified miR-155 target genes, we performed an over-representation analysis (FDR adjusted ( 40 )) using the online pathway enrichment analysis tool Genetrail 3.0 ( 27 ). Six out of the 17 identified targets (DDX17, EZH1, JMY, KDM5B, TADA2B, TAF7) were significantly enriched in the GO molecular function term ‘transcription coregulator activity’ ( P = 6.89E−04).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the functions of the identified miR-155 target genes, we performed an over-representation analysis (FDR adjusted ( 40 )) using the online pathway enrichment analysis tool Genetrail 3.0 ( 27 ). Six out of the 17 identified targets (DDX17, EZH1, JMY, KDM5B, TADA2B, TAF7) were significantly enriched in the GO molecular function term ‘transcription coregulator activity’ ( P = 6.89E−04).…”
Section: Resultsmentioning
confidence: 99%
“…These were then combined using standard hierarchical clustering with Ward's minimum variance method ( 26 ). In both clustering steps, we use the Euclidean distance for the gradients of two consecutive time points as a distance measure ( 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…Seurat default Log (fold change) > 0.25 (absolute value), adjusted P value (Bonferroni correction) < 0.05, and expression in greater than 10% of cells were required to consider a gene differentially expressed. Biological pathway and gene ontology enrichment analysis was performed using Enrichr 155 , Metascape 156 , or GeneTrail 3 157 with input species set to Homo sapiens 156 and using standard parameters. Docking, processing, and viral defense genes relevant to SARS-CoV-2 were chosen based on ladecola, et al 16 .…”
Section: Methodsmentioning
confidence: 99%
“…The datasets for each tissue were then compared in order to study the intersection of pathways. In addition, enrichment analysis was performed based on gene ontology (GO) biological process using the tool GeneTrail3 [ 17 ], which takes as input the lists of DEGs along with their log 2 FC values. The unweighted version of the gene set enrichment analysis (GSEA) was used, which is a non-parametric hypothesis test that sorts the input list of genes based on their expression values.…”
Section: Methodsmentioning
confidence: 99%
“…Thus far, studies of gene expression at the RNA level have been performed in human tissues and different ataxia mouse models. These studies concluded to a number of candidate involved biological pathways, including glutamate signaling, calcium signaling, synaptic transmission, DNA repair pathways, cell cycle, metabolic processes, and receptor-mediated signaling pathways [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. To our knowledge, none of the above studies or any other study at the whole or coding transcriptome expression level, aimed to identify implicated pathways for SA.…”
Section: Introductionmentioning
confidence: 99%